Faxén’s law for arbitrary oscillatory Stokes flow past a porous sphere - Prakash, J.; Raja Sekhar, G.P.; Kohr, M. (Archives of Mechanics, 2012)
The present article deals with the study of the hydrodynamics of a porous sphere in an oscillatory viscous flow of an incompressible Newtonian fluid. Unsteady Stokes equations are used for the flow outside the porous sphere and Darcy’s equation is used for the flow inside the porous sphere. Corresponding Faxén’s law for drag and torque acting on the surface of the porous sphere is derived. Also the results are compared with few existing special cases. Examples like uniform flow, oscillating Stokeslet, oscillatory shear flow and quadratic shear flow are discussed.